Memahami Indonesia - Sarjadi, Soegeng, 1942-; Rinakit, Sukardi (Jakarta : Soegeng Sarjadi Syndicate, 2006)
Socioeconomic and political issues in Indonesia
[References]: p. 389-395
Keywords: Indonesia -- Politics and government -- History; Indonesia -- History